FAKTOR YANG MENYEBABKAN TERJADINYA TINDAK PIDANA ILEGAL LOGGING BERDASARKAN UNDANG – UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - Kartika Agus Salim (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2022)
Illegal logging is defined to forest damage by individuals or groups of people, either jointly by logging trees, loading, unloading, removing, transporting, controlling, owning, possessing, controlling, unloading, distributing, illegally smuggling, receiving, buying, selling, exchanging, receiving deposits, and an illegal timber forest product. According to a forestry observer and environmental, the various natural disasters have occurred as a result of forest destruction as or illegal logging. The method of this research is sociological empirical legal research. It is carried out by examining primary data, which is obtained directly at the field.The culture factors, which means human attitudes and legal systems of belief, thought values, and expectations. The mood of the social mind that determines how the law is used, avoided, or misused. Thus, these factors are caused by a lack of public awareness toward the importance of law.There are obstacles and solutions done by officials involved in forest protection efforts in Melawi Regency, namely (1) The communities in middle to lower economic level at Melawi Regency(1) The extent of the forest zone (3) CommunityThe Solutions done by officials involved in forest protection (1) Community Outreach (2) A Forest routinely Patrols (3) Building the awareness of villager toward environment.The government must formulate job opportunities for people living around forests to prevent the illegal logging. The forests law enforcement officials should be keen in deploying personnel due to law enforcement process efficiently.